Effectiveness of Interventions Targeting Health Behaviors in University and College Staff: A Systematic Review. Issue 5 (May 2015) - Plotnikoff, Ronald; Collins, Clare E.; Williams, Rebecca; Germov, John; Callister, Robin
Objective: Evaluate the literature on interventions targeting tertiary education staff within colleges and universities for improvements in health behaviors such as physical activity, dietary intake, and weight loss. Data Source: One online database, Medline, was searched for literature published between January 1970 and February 2013. Study Inclusion and Exclusion Criteria: All quantitative study designs, including but not limited to randomized controlled trials, quasi-experimental studies, nonrandomized experimental trials, cohort studies, and case-control studies, were eligible. Data Extraction: Data extraction was performed by one reviewer using a standardized form developed by the researchers. Extraction was checked for accuracy and consistency by a second reviewer. Data Synthesis: Data in relation to the above objective were extracted and described in a narrative synthesis. Results: Seventeen studies were identified that focused on staff within the tertiary education setting. The review yielded overall positive results with 13 reporting significant health-related improvements. Weight loss, physical activity and fitness, and/or nutrition were the focus in more than half (n = 9) of the studies. Conclusion: This appears to be the first review to examine health interventions for tertiary education staff. There is scope to enhance cross-disciplinary collaboration in the development and implementation of a "Healthy University" settings–based approach to health promotion in tertiary education workplaces. Universities or colleges could serve as a research platform to evaluate such intervention strategies.